2020
DOI: 10.34119/bjhrv3n5-088
|View full text |Cite
|
Sign up to set email alerts
|

Pré-natal na zona rural, norte da Bahia - BA: Perfil de gestantes atendidas em consultas de enfermagem / Prenatal care in the rural area, in northern Bahia -BA: Pregnant women profile attended at the nursing consultations

Abstract: RESUMO O objetivo foi traçar o perfil sócio-econômico e obstétrico das grávidas atendidas em consultas de enfermagem no distrito de Maniçoba pertencente a Juazeiro-BA. Trabalho tem abordagem quantitativa, natureza exploratória e descritiva a partir de uma análise documental retrospectiva em 61 fichas de pré-natal, no período de junho de 2018 a janeiro de 2019. O perfil demonstrou que grande parte das gestantes são primigestas (49%), trabalhadoras rurais (40,98%), católicas (18%), estão dentro da faixa etária d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…At the national level, research carried out in the north of Bahia identified black or brown pregnant women with inadequate prenatal care, absence of a companion in the maternity ward, pilgrimage through maternity hospitals to receive specialized care and less instruction on the process of pregnancy, birth and in-hospital care ( 17 ) .…”
Section: Discussionmentioning
confidence: 99%
“…At the national level, research carried out in the north of Bahia identified black or brown pregnant women with inadequate prenatal care, absence of a companion in the maternity ward, pilgrimage through maternity hospitals to receive specialized care and less instruction on the process of pregnancy, birth and in-hospital care ( 17 ) .…”
Section: Discussionmentioning
confidence: 99%